Análise da cobertura espacial dos instrumentos utilizados pela SUDENE para a promoção da política nacional de desenvolvimento regional - Ferreira, Wendel Mendes (2024)
The National Policy for Regional Development (PNDR) aims to promote convergence of intra and inter–regional levels of development and quality of life in the country and equal access to development opportunities in regions with low socioeconomic indicators. To this end, two important instruments administered by the Superintendence for the Development of the Northeast (Sudene) are the granting of tax incentives through the reduction of Corporate Income Tax (IRPJ) and the financing of projects with resources from the Northeast Development Fund (FDNE). Given this scenario and considering the incipient literature on the Fund, an exploratory analysis of the spatial data of the two instruments mentioned was carried out, as well as the calculation of their spatial correlation with a Municipal Development Index. For this, the location of the municipalities whose territory has projects benefiting from any of these instruments of the regional policy was considered, using the calculation method of the Moran index (1948). Furthermore, a spatial regression model was estimated relating the level of municipal development with the receipt of the two instruments. The results show a positive correlation between the number of requests for tax benefits granted to municipalities in the region where Sudene operates and FDNE investments. Moran's scatter map shows that there are few regions (clusters) where this relationship is higher, which are located around regions that are already economically developed, notably the capitals of Ceará and Espírito Santo, thus distancing themselves from the guidelines of the regional development policy, in comparison to the areas in the interior of Sudene. Furthermore, a direct effect on development was observed only of tax incentives, while FDNE was only relevant in explaining variations in municipal GDP per capita.